A Brief Analysis of Vocabulary Teaching in Teaching Chinese as a Second Language - Temmy, Temmy (Lingua Cultura, 2014)
The goal of the article was to develop Mandarin vocabulary teaching material for Indonesian people and foreigners. Teaching material was developed by cutting vocabulary, called Chunk theory. Article clarified Chunk theory, basic strategy of teaching Chunk theory, and the basic idea of teaching Chunk theory; gave opinions and some important factors related to Chunk theory. It can be concluded that there is a significant factor in teaching Chunk theory, that is, a meaning transformation process to different context. It can be more (Chunk Up), less (Chunk Down), and similar (Chunk Laterally).